THE FEDERAL RESERVE'S DUAL MANDATE AND THE INFLATION‐UNEMPLOYMENT TRADEOFF. - Kaya, Ayse; Golub, Stephen; Kuperberg, Mark; Lin, Feng (Contemporary Economic Policy, 2019)
Using Federal Open Market Committee (FOMC) transcripts from 1960 to 2010, this paper examines the evolution of the Committee's approach to the inflation‐unemployment tradeoff. We find: (1) FOMC discussions have increasingly emphasized inflation relative to unemployment and (2) this shift occurred during the Volcker era and has continued even as inflation itself declined, with the result that the emphasis on inflation has become entrenched and disconnected from actual inflation. Finally, we create an expanded Taylor Rule that includes these FOMC discussions and find that the increased emphasis on inflation is positively correlated with the federal funds rate.